Cooperative Interaction of Phenolic Acids and Flavonoids Contained in Activated Charcoal with Herb Extracts, Involving Cholesterol, Bile Acid, and FXR/PXR Activation in Broilers Fed with Mycotoxin-Containing Diets - Ying Zhang; Zishen Lin; Lixue Wang; Xiangyue Guo; Zhihui Hao; Zhen Li; Lee J. Johnston; Bing Dong (MDPI AG, 2022)
The charcoal-herb extract complex (CHC) is a product of activated charcoal sorption of herb extracts that contain phenolic acids and flavonoids. The effective dose of CHC to promote animal growth is about one tenth of effective dosage of activated charcoal. The purpose of this study was to evaluate potential cooperative interactions between activated charcoal and herb extracts. Two feeding experiments were conducted. In Experiment 1, a responsive dose of CHC to broiler growth was determined to be 250 mg/kg of the diet. In Experiment 2, CHC increased growth performance and improved meat quality, but decreased indices of oxidative stress and inflammation as compared with similar doses of activated charcoal or herb extracts. CHC also increased concentrations of serum cholesterol, bile acid in the gallbladder, and bile acid in feces. The herb extracts present in CHC were largely represented by phenolic acids (PAs, caffeic acid, and vanillin) and flavonoids (FVs, daidzein, and quercetin-D-glucoside) in the detoxification activity of CHC in a mouse rescue test when the mice were gavaged with T-2 mycotoxin. PAs and FVs significantly increased the expression of CYP7A1, PXR, CYP3A37, Slco1B3, and Bsep in chicken primary hepatocytes. In conclusion, CHC integrated the cooperative interactions of activated charcoal and herb extracts via the FXR/RXR-PXR pathway to detoxify mycotoxins.